Future Scenarios for Iraqi Foreign Policy: Between Bias and Neutrality (قضايا سياسية, 2025)
The study focuses on future scenarios for Iraqi foreign policy, between alignment and neutrality. The results highlight that alignment with an external axis may provide short-term support, but it restricts the independence of national decision-making and exacerbates challenges. Positive neutrality, on the other hand, provides an opportunity to enhance Iraq's sovereignty, diversify its partnerships, and enhance its regional role as a mediator. Negative neutrality, on the other hand, leads to a decline in Iraq's regional and international role and increases the fragility of national politics. The study concludes that adopting a policy of positive neutrality is the most appropriate option for achieving a balance between protecting sovereignty and enhancing Iraq's regional and international standing.